Importance of Social Acknowledgment in Treatment of Clients with War Trauma Experience - Pantić, Zdenka; Priebe, Stefan; Ljubotina, Damir Frančišković, Tanja; Mladić, Martina (2005)
Here we present results of a longitudinal study whose main goal was to assess treatment outcomes in people with war trauma included in formal psychotherapy and factors related with treatment outcomes. The whole sample consisted of 174 war veterans and 45 refugees situated in Croatia undergoing formal psychotherapy. All clients were interviewed at baseline and followed up after 3 and 12 months. This paper focuses on the importance of clients' perception of social acknowledgment. Preliminary results show that war veterans percieve extremely low levels of acknowledgment. 40, 4% of veterans percieve that family members don't understand their problems and don't acknowledge what they survived. 65, 5% give the same answers for their friends, 88, 2% for other people they know, 92, 8% for persons in administrative institutions, and 95, 4% for the government. Results show that refugees perceive somewhat higher levels of social acknowledgment than war veterans. Results indicate low but statisticaly significant correlations between low social acknowledgment and some measures of treatment outcomes. The findings indicate an impact of psychosocial context on efficacy of treatment for clients with war related trauma experiences. Posttraumatic environment is still highly stressful for traumatized persons and thus interferes with the therapist’ s efforts pointed at trauma integration. Recognition and identification of these factors is of high relevance for the better understanding of the therapeutic process, especially the evaluation of therapy, both on an individual and group level.
Projekt MZOS
ENG